Exploring the Unique Morphological and Syntactic Features of Singlish (Singapore English) - Nourma Silvia Ningsih; Fadhlur Rahman (Journal of English in Academic and Professional Communication, 2023)
Singapore is home to a number of significant ethnic groups, including Chinese, Malay, and Tamil, whose contributions have shaped the distinctive characteristics of Singlish in comparison to standard English. This study aims to examine the morphological and syntactic characteristics of Singlish, an English-based creole spoken in Singapore, emphasizing its impact on interethnic communication. Using comparative analysis, Singlish's morphological and syntactic characteristics were compared to those of standard English and the languages of the three largest ethnic groups in Singapore (Chinese, Malay, and Tamil). Examining grammatical patterns, word order, sentence structure, and the use of particular linguistic features would be required. The findings demonstrate that Singlish utilizes distinctive syntactic patterns that frequently incorporate Malay, Chinese, and Tamil grammatical formulas. Singlish, in contrast to standard English, lacks subject and object pronouns and frequently employs "sentence-ending particles" such as what, leh, lor, hah, and meh, in addition to lah. In addition, the copula be is frequently omitted before adjectives, nouns, and locatives in Singlish. In addition, the presence of word repetition and word drop in Singlish can be traced back to the Chinese dialect Hokkien. The Singaporean government has attempted to discourage the use of Singlish; however, this has sparked controversy due to the significance of the language in interethnic communication and its reflection of interethnic identity. As a result, Singlish is a fascinating subject for linguistic and sociological study, with significant implications for language education and policy.